The Paradigm of the Sakinah Mawaddah Wa Rahmah Family and Its Relationship to Divorce Rates and Population Growth in Indonesia - Sifa Mulya Nurani; M.Muhsin (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The divorce rate in Indonesia reached 2,266 cases in 2019-2020. Indicating that the Sakā “nah Mawaddah wa Raá¸¥mah Paradigm in the normative constellation of Islamic family law studies, has not been implemented properly by family couples. This study aims to describe the relationship of the Sakā “nah Mawaddah wa Raá¸¥mah family paradigm in the context of Islamic psychology with the divorce rate and population growth in Indonesia. This type of research is qualitative library research, which explores Islamic family law research with descriptive studies. The research data is in the form of literature that reviews the Sakā “nah Mawaddah wa Raá¸¥mah family paradigm. Data collection techniques with documentation. While data analysis is done by data reduction, data presentation, and data analysis. The results showed that the Sakā “nah Mawaddah wa Raá¸¥mah family paradigm has a significant relationship to two cases, divorce and population growth. In order to prevent divorce, the derivative of this paradigm provides a resolution; strengthen religion, mutual trust between families, fulfill rights and obligations, meet each other, and instill a sense of love and love. Meanwhile, preventive efforts derived from this paradigm to overcome population growth can be done by instilling a sense of peace in the family, love, and participating in the success of government programs such as the Preparation of Family Life for Teenagers (PKBR).